Relationship of Perceived Environmental Characteristics to Leisure-Time Physical Activity and Meeting Recommendations for Physical Activity in Texas - Holahan, Carole K. (Centers for Disease Control and Prevention, 2008)
INTRODUCTION: We investigated the relationship of perceived environmental characteristics to self-reported physical activity in Texas adults using 2004 Behavioral Risk Factor Surveillance System data. METHODS: The 2 research questions were, "Are perceived neighborhood characteristics and reported use of facilities associated with self-reported leisure-time physical activity for male and female Texas residents aged 18 to 64 years?" and "Are perceived neighborhood characteristics and reported use of facilities related to meeting recommendations for moderate to vigorous physical activity for Texas men and women aged 18 to 64 years?" Descriptive statistics and multiple logistic regression were used for the analyses. RESULTS: Multiple logistic regression analyses controlling for sociodemographic factors showed that for women, perceptions of neighbors being physically active, pleasantness of the neighborhood, lighting, safety, and feelings of neighbor trustworthiness were associated with leisure-time physical activity. Several of these variables were also related to meeting recommendations for physical activity. Reports of use of several types of neighborhood facilities were related to men's and women's leisure-time physical activity and with meeting recommendations for physical activity for women. CONCLUSION: Perceptions of neighborhood characteristics and reported use of facilities were related to physical activity and to meeting recommendations for physical activity, with stronger associations for women than for men. Interventions to increase levels of physical activity among Texans should be informed by multilevel assessments including environmental characteristics and by attention to important subpopulations.